A GIS analysis to target priority areas for adoption of five multipurpose tree species in Ethiopia, Kenya and Uganda - Conchedda, Giulia; Berhe, Kahsay; Jabbar, M.A. (2001)
The Multipurpose Tree (MPT) species can fit into the farming systems of the East African region where low agricultural productivity, widespread land degradation and hence a diminishing capacity to support the growing human and livestock population are major problems. GIS has been used to develop a spatial representation of the likelihood of adoption of five NTT species (Calliandra Calothyrsus, Sesbania sesban, Leucaena diversifolia, L. pallida and Chamaecytisus palmensis) by combining digital layers of land cover, human and cattle population densities within their agro-ecologically suitable areas in Ethiopia, Kenya and Uganda.